2021
DOI: 10.3389/fpls.2021.809506
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Huanglongbing Detection Based on Multi-Modal Feature Fusion Learning

Abstract: Citrus Huanglongbing (HLB), also named citrus greening disease, occurs worldwide and is known as a citrus cancer without an effective treatment. The symptoms of HLB are similar to those of nutritional deficiency or other disease. The methods based on single-source information, such as RGB images or hyperspectral data, are not able to achieve great detection performance. In this study, a multi-modal feature fusion network, combining a RGB image network and hyperspectral band extraction network, was proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The investigation of Nagasubramanian et al (2019) demonstrated that soybeans infected the charcoal rot are more sensitive than healthy soybeans in the wavelengths of visible spectra (400–700 nm). Yang et al (2021) have achieved good results in the Citrus Huanglongbing detection task by fusing hyperspectral data in CNNs using a multimodal approach. Recent research has shown that the transformer architecture is better suited for multimodal tasks ( Frank et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of Nagasubramanian et al (2019) demonstrated that soybeans infected the charcoal rot are more sensitive than healthy soybeans in the wavelengths of visible spectra (400–700 nm). Yang et al (2021) have achieved good results in the Citrus Huanglongbing detection task by fusing hyperspectral data in CNNs using a multimodal approach. Recent research has shown that the transformer architecture is better suited for multimodal tasks ( Frank et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We consider transforming the optimized post reflection spectral curve into an image with rich feature information through certain methods, and then using deep learning to train image processing. Yang et al of Zhejiang University extended the two-dimensional spectrum horizontally into a three-dimensional map which is shown in Figure 3 and substituted it into the deep learning model training in 2021 [9] . The experiment achieved high accuracy, but the extra one-dimensional did not carry other characteristic information.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…Here is a sample illustration and caption for a multimedia file: Figure 3. Reflectivity cylindrical pseudo image [9] .…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…On the other hand, CNN-based systems usually detect four classes, including HLB, healthy, mineral deficiencies (e.g., magnesium, nitrogen, and zinc) [18], [20], [22], and other diseases (e.g., canker and greasy spot) [21]. Moreover, only one CNN-based approach distinguishes between HLBpositive and HLB-negative classes in orange crops [30].…”
Section: Literature Reviewmentioning
confidence: 99%